2016
DOI: 10.1007/s13157-016-0786-z
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Buffer Assessment Fails to Predict and Classify Wetland Floristic Quality in Oklahoma

Abstract: Rapid field assessment indicators of ecological stress and disturbance may or may not reflect actual biological conditions. We tested the ability of rapidly assessed buffer quality to predict and classify wetland floristic quality across 106 sites in Oklahoma, USA. We used buffer zone metrics from a national-level rapid assessment tool (USA-RAM) to evaluate applicability at the state level. The rapid assessment relying on buffer quality did not relate predictably (linearly) with floristic quality, but the rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…Results from regional studies show mixed results regarding the strength of associations between wetland biota and human activities adjacent to wetlands and those at a larger landscape scale. Based on a study of 55 wetlands in the US Interior Plains state of Oklahoma, for example, Bried et al (2016) reported that the site-scale buffer disturbance evaluated by the NWCA disturbance index (140m-HDAI) was not a good predictor of the condition of wetland vegetation. In some regions, however, floral or faunal assemblages may be more strongly influenced by the type and proximity of overt human activities assessed by the NWCA disturbance measures.…”
Section: Discussionmentioning
confidence: 99%
“…Results from regional studies show mixed results regarding the strength of associations between wetland biota and human activities adjacent to wetlands and those at a larger landscape scale. Based on a study of 55 wetlands in the US Interior Plains state of Oklahoma, for example, Bried et al (2016) reported that the site-scale buffer disturbance evaluated by the NWCA disturbance index (140m-HDAI) was not a good predictor of the condition of wetland vegetation. In some regions, however, floral or faunal assemblages may be more strongly influenced by the type and proximity of overt human activities assessed by the NWCA disturbance measures.…”
Section: Discussionmentioning
confidence: 99%
“…Ecoregions are well established throughout the United States and capture broadly consistent climate‐soil‐vegetation‐landcover patterns over large areas (Stoddard, ). We previously found that splitting the CGP from other ecoregions helped to model wetland floristic quality and had more impact than separating depressional wetlands from riverine, seep, and lacustrine‐fringe wetlands (Bried et al, ; Jog et al, ). Others have recommended ecoregional specification of depressional wetland floristic quality in Oklahoma (Gallaway, Davis, Dvorett, & Tramell, ).…”
Section: Discussionmentioning
confidence: 99%
“…Plant checklists were accumulated from one‐time surveys (during 2012–2016) of 117 nonforested wetlands (Figure ). Sites were located from a variety of sources and spanned nine ecoregions, several major wetland classes, and a range of human disturbance (Bried et al, ; Jog et al, ). Many sites were targeted in the large depression‐rich Central Great Plains ecoregion (Figure ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations